Defining Cyanobacterial Species: Diversity and Description Through Genomics. (3rd March 2020) - Willis, Anusuya; Woodhouse, Jason N.
Abstract: Cyanobacteria were the first oxygenic photosynthersizers, evolving ∼3.5 bya, they have since radiated into one of the most diverse and widely distributed phyla of bacteria. Cyanobacterial diversification occurs through ecological adaptation, facilitated by asexual reproduction, homologous recombination and horizontal gene transfer, and selection pressures on ecotypes leading to speciation. Delimiting cyanobacterial species is, thus, fraught with difficulties and a clear taxonomy has not yet been universally accepted. This review discusses diversity and description of cyanobacteria: covering traditional and new methods to define species boundaries and concluding with a focus on the advances made through genomics. Examples from the genera Raphidiopsis, Microcystis, and Prochlorococcus are used throughout. Genome plasticity allows cyanobacteria to rapidly adapt and be resilient to environmental changes, illustrating the means of their persistence, and is an important aspect of their biology. Genomics has revealed generalist and specialist genome strategies, intraspecific diversity, and genome evolution in response to environmental stimuli. New taxonomic definitions will need to account for intraspecific genetic variation, with a species classification that is relevant to a species concept and scientific endeavors. Capturing intraspecific diversity with comparative genomics may provide a new path to species classification. This is demonstrated with two case studies; comparison of available genomes shows differing species delineation of Raphidiopsis and Microcystis . In both genera, species boundaries occur at ∼96% average nucleotide identity (ANI), where homologous recombination is constrained, but speciation of Raphidiopsis raciborskii, R. brookii, and R. curvata has occurred through geographic isolation, whereas available data on Microcystis contain at least 15 species, reflecting, to differing extents, different ecotypes, which may co-exist. Both case studies question the relative importance of species-specific versus habitat specific gene pools as drivers of inter- and intraspecific diversity.